Hubungan Penggunaan Popok Instan terhadap Kejadian Ruam Popok pada Balita Usia 0-3 Tahun di PMB Ani Mahmudah SST Kab. Lamongan - Asyaul Wasiah; Ida Susila; Salma Nabila (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2021)
Diaper rash is a skin problem in the genital area of ​​infants and toddlers, which is characterized by the appearance of red patches on the skin. Baby's skin is still sensitive because its functions are still developing, especially in the epidermis or the outermost layer of the skin which provides natural protection for the skin from the surrounding environment. Continuous use of diapers for too long will increase the sensitivity of the baby's skin so that it can cause skin irritation. That's why baby's skin is more sensitive and prone to skin disorders. Disorders that usually arise in the form of a skin rash known as diaper rash or diaper rash. The purpose of this study was to determine the relationship between the use of instant diapers and the incidence of diaper rash in toddlers aged 0-3 years at PMB Ani Maheasy SST, Kab. Lamongan Year 2021. The design in this research is an observational analytic with a cross sectional design. The population in this study were all toddlers aged 0-3 years at PMB Ani Maheasy, SST Lamongan from January to February 2021. A sample of 29 people was obtained using the Simple Random Sampling technique. The independent variable is diaper use and the dependent variable is the incidence of skin irritation. The instrument used was a questionnaire sheet in the form of a checklist regarding the variables of diaper use and the incidence of skin irritation compiled by researchers who had conducted validity and reliability tests, then the results were analyzed using the chi square test with a significant level of = 0.05. Based on the results of statistical tests using the Chi-square value, the results of p value: 0.000 < α:0.05 indicate that there is a relationship between the use of instant diapers and the incidence of diaper rash in toddlers aged 0-3 years at PMB Ani Maheasy SST, Kab. Lamongan Year 2021. p value: 0.000 < α:0.05. The solution for using diapers with skin irritation in toddlers is by washing their hands with regular soap before touching the baby's genitals, and the mother's behavior in playing an important role in caring for the little one should check the baby's diaper as often, if skin irritation occurs, apply a cream/ointment to prevent irritation. It is expected that existing health workers such as posyandu cadres can provide information about how to use instant diapers properly, such as information about when is the right time to change diapers and the right type of diaper to use on babies to avoid rashes in babies as a result of using instant diapers.